TERMINALIA ARJUNA - A NEW HOST OF PHILOSAMIA RICINI ERI SILKWORM UNDER WESTERN MAHARASHTRA CONDITION - KAVANE R.P. (International Journal of Pharma and Bio Sciences, 2015)
An attempt was made to rear the eri silkworm, Philosamia ricini on the leaves of Terminalia arjuna (Arjun) for the first time in India and reared under laboratory condition. It was observed that the arjun is a potential new host of eri silkworm. The growth parameters and cocoon characters of the eri silkworm reared on arjun leaves were normal. The eri silkworm successfully lasted its life cycle ranged from 52 to 55days. The effective rate of rearing, weight of pre-spinning larvae, cocoon, shell and pupae ranged from 40 to 45 per cent, 6 to 7 g, 2.80 to 2.90 g, 0.40 to 0.42 g, 2.35 to 2.40g, respectively. Parameters such as length of cocoon shell, width of shell, shell thickness, etc. The fecundity ranged from 400 to 425 eggs. The finding of arjun as a potential new host for eri silkworm has opened new vistas in promoting vanya silk industry.